KEBERADAAN BURUNG SEBAGAI ATRAKSI EKOWISATA DI KAWASAN BUMI PERKEMAHAN CEKIK TAMAN NASIONAL BALI BARAT - Ida Bagus Made Suaskara; I Ketut Ginantra; A. A. Gde Raka Dalem (Bumi Lestari Journal of Environment)
study on birds as Ecotourism attractions was conducted on August-September 2006in Cekik Camping Ground, West Bali National Park, Bali-Indonesia. Explorations methodwas utilised to find out bird species observed in the field. Indentification of birds species wasundertaken based on MacKinon (1993). Their status were determined based on IndonesiaRegulation (PPRI) No. 7, 1999. Results of this study indicated that in Cekik area wereidentified 36 bird species that were included in 20 families. The dominant species weremember of the family of Sylviidae (6 species), Nectaridae, Columbidae and Dicruridae (3species respectively). Three species of birds observed on the site were protected by IndonesiaRegulation: Brown-throated Sunbird (Anthreptes malacensis), Olive-backed Sunbird(Nectarinia jugularis) and Green banded Kingfisher (Alcedo euryzonia). Perspectiveutilization of bird for ecotourist (bird watching) attractions in this area was related to therichness of the birds species, their status, activities and interaction with vegetation or ontheir habitats. The bird activity which might become ecotourist attractions including:foraging, perching, migration and nesting.